The Role of Patience and Tawakkal in Achieving the Sustainable Development Goals (SDGs) - Hamdan, Hamdino (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2021)
In the effort towards achieving the goal of sustainable development through business activities carried out to ensure the positive impact can be felt by the community in ending poverty, sometimes, we are constantly tested by Allah s.w.t. with tests coming alternately. Although we often maintain a relationship with Him, we are not immune to trials. Sometimes it may tickle in our hearts, why God is constantly testing us with various challenges and hardships. Only by tawakkal (trusting) in Allah s.w.t. we can gain Allah S.W.T.'s attention in facilitating our efforts towards achieving the goal of sustainable development through business activities based on the ‗social enterprise‘ approach.